Effects of Multiple Karenia brevis Red Tide Blooms on a Common Bottlenose Dolphin (Tursiops truncatus) Prey Fish Assemblage: Patterns of Resistance and Resilience in Sarasota Bay, Florida - Berens McCabe, Elizabeth J.; Wells, Randall S.; Toms, Christina N.; Barleycorn, Aaron A.; Wilkinson, Krystan A.; Palubok, Valeriy I. (Frontiers in Marine Science, 2021)
Red tide blooms caused by the toxic dinoflagellate Karenia brevis are natural disturbance events that occur regularly along Florida’s west coast, often resulting in massive fish kills and marine mammal, seabird, and sea turtle mortalities. Limited prior work on the ecological effects of red tides suggests they play an important role in structuring ecosystem dynamics and regulating communities, however specific effects on prey populations and potential alterations to predator-prey interactions are unknown. We surveyed the prey fish assemblage of a top marine predator, the common bottlenose dolphin (Tursiops truncatus), in shallow seagrass habitat in Sarasota Bay, Florida, during 2004-2019, collecting data on prey density, species composition, K. brevis cell densities, and environmental variables. Across eight distinct red tide bloom events, resistance, resilience, and the ecological effects on the prey assemblage varied depending on bloom intensity, season, and frequency. Prey assemblage structure showed significant and distinct short-term shifts during blooms independent of the normal seasonal shifts in prey structure seen during non-bloom conditions. Canonical correspondence analysis indicated a strong influence of K. brevis density on assemblage structure. Blooms occurring primarily in the summer were associated with less initial prey resistance and higher than average annual catch per unit effort (CPUE) 1-3 years following bloom cessation, with bloom frequency prolonging the time needed to reach higher than average annual CPUE. Regardless of season, recovery to pre-bloom prey abundances occurred within one year. Sample-based rarefaction and extrapolation indicated significant differences in prey diversity among summer bloom events. This study is a first step in identifying differences in resistance, resilience, and the ecological effects of multiple red tide bloom events of various temporal scales and intensity on a dolphin prey assemblage. Improved understanding of the influence of red tides on estuarine structural dynamics and function can better inform management, and potentially guide mitigation efforts post-bloom.